Potassium nitrate and pericarp removal in germination and in evaluation crambe seed vigor - Anísio da Silva Nunes; Luiz Carlos Ferreira de Souza; Silvana de Paula Quintao Scalon (Semina: Ciências Agrárias, 2015)
The objective of this study was to evaluate the potassium nitrate influence (KNO3) and the pericarp removal in germination, as well as the viability of the electrical conductivity test for evaluation crambe seed vigor. The experimental design used in the two trials was completely randomized design with treatments arranged in a 2x2x4 factorial in the germination test (with and without KNO3, with and without pericarp and four lots of seeds) and 2x4 factorial in the tests and emergency electrical conductivity (with and without pericarp and four seed lots). The potassium nitrate concentration (KNO3) in the wetting of the substrate solution was 0.2% and the pericarp removal has been performed manually. Evaluations were made of moisture content, final germination, first counting, germination speed index, root and shoot length, total dry mass and seedling emergence and electrical conductivity. Potassium nitrate does not increase the percentage or the germination rate of crambe seed. The manual removal of the pericarp increases the speed, but does not affect the germination of seeds. The electrical conductivity can be recommended to identify vigor differences among seed lots of crambe.